2017
DOI: 10.1080/15374416.2017.1295383
|View full text |Cite|
|
Sign up to set email alerts
|

The Cognitive, Affective, and Somatic Empathy Scales (CASES) for Children

Abstract: Although the assessment of empathy has moved from general empathy to differentiating between cognitive and affective empathy, no instruments have assessed somatic (motor) empathy, and none have separated positive from negative affect empathy. The main objective of this study was to develop a 30-item self-report cognitive, affective, and somatic empathy scale (CASES) with positive and negative affect components for use with children and adolescents. A community sample of 428 male and female 11-year-olds complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 55 publications
7
47
1
1
Order By: Relevance
“…Consistent with the prior study , we found sex differences in empathy with moderate to strong effect sizes. Of note, the means of the empathy scores in the current study were very similar to those in Raine and Chen (2018), with cross-study correlations revealing similar associative patterns between empathy scores and related constructs (e.g., CU scores, sex differences). The current study provides support for the multifaceted nature of empathy which can be captured in a brief self-report instrument, and the cross-culture generalizability of this instrument to an Asian culture.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Consistent with the prior study , we found sex differences in empathy with moderate to strong effect sizes. Of note, the means of the empathy scores in the current study were very similar to those in Raine and Chen (2018), with cross-study correlations revealing similar associative patterns between empathy scores and related constructs (e.g., CU scores, sex differences). The current study provides support for the multifaceted nature of empathy which can be captured in a brief self-report instrument, and the cross-culture generalizability of this instrument to an Asian culture.…”
Section: Discussionsupporting
confidence: 67%
“…We established cross-cultural generalizability by replicating the findings of the confirmatory factor analyses of the CASES from Raine and Chen (2018). Attention is warranted that the CFIs of all the nested models are generally lower than the set criteria of .90, which suggested that the proposed model did not fit the data as well as we hope.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It appeared that employing a measure that incorporated both affective and cognitive components of empathy and examining them in parallel was the most appropriate, particularly as the relationship between these components and their development in childhood remained a complex issue (Raine & Chen, 2018). The use of the Thinking and Feeling Questionnaire allowed for the examination of the possible interactive effects of affective and cognitive empathy.…”
Section: Affective Empathymentioning
confidence: 99%